Research of Load Sharing Performance of Hub Reducer with Considering the Flexible of Planetary Pin - Li Xuan (Jixie chuandong)
Taking the distributed electric drive hub reducer as study object，by using the FEA method, the support stiffness of the planetary wheel bearing and the flexible pin is solved. The obtained support stiffness are introduced into the lumped parameter dynamics model, a dynamics model that comprehensively considers the planetary pin shaft flexibility, time-varying mesh stiffness, time-varying mesh damping and comprehensive error is established. The relationship between the load sharing coefficient and the comprehensive error and the pin flexibility is explored. Moreover, by comparing the load sharing coefficient of the planetary transmission system under two planetary pin support structures, it shows that the proposed flexible pin structure can improve the system load sharing performance. The results provide a theoretical basis for the performance improvement and structural optimization of planetary gearbox.